Design Gamification Applications in Mathematics Learning Using Augmented Reality - Muslih Hasan Pambudi; Emi Pujiastuti; Sugiman Sugiman; Amin Suyitno (Universitas Negeri Semarang, 2022)
Abstract. Students grow up with digital technologies so that they have new attitudes and learning styles for learning. Gamification enhances the involvement of students with the material and problems encountered. In this papper, we reflect on the design of gamification experience in mathematics learning using augmented reality for helping students understand and solve real world problems. We focus on designing applications for game-based learning and solving real-world problems for learning environments. This study uses Research and Development (R&D) with the ADDIE model (analyze, design, develop, implement, and evaluate). This study focuses in analyze, design, and develop step. The result of this study is the first feature of the application is facilitating the students to measure the real-world object using digital measuring tools, the second feature of the application is facilitating the student to explore real world problems that accompanied by a virtual pet through augmented reality then get credits points for solving the problems and use the point to upgrage the virtual pet . The limitation of this study is the application needed a special operating system to operate properly, the device needed AR Core embedded device. Our finding that designing gamefy application needed careful consideration of game features to enhance the students’ involvement and intentive in mathematics learning with excitement.